Impact of Severe Preeclampsia on the Incidence of Low-Birth-Weight Babies (Majalah Kedokteran Bandung, 2023)
Infant birth weight is an important indicator of survival, growth potential, and developmental capacity. Maternal health plays an important role in determining the well-being of newborns. A complicated pregnancy, inclusive of conditions such as preeclampsia, elevates the risk of giving birth to a low birth weight (LBW) baby. This study aimed to compare the impact of severe preeclampsia on the incidence of LBW babies in Dr. Dradjat Prawiranegara General Hospital Serang, Indonesia. This case-control analysis included 148 parturients recruited randomly from June to October 2022. Logistic regression was used as the analytical tool, with P=0.000 considered as demonstrating a significant association. The incidence rates of LBW and severe preeclampsia in 2018 were 19.84% and 14.15%, respectively. The case group recorded LBW within the weight range of 1,000-2,450 g, with 38% of them were Small for Gestation Age (SGA), while 50% and 12% were Appropriate for Gestational Age (AGA), and Large for Gestational Age (LGA), respectively. In contrast, the control group, with birth weights ranging from 2,600-4,500 g, 13.50% were SGA, while 77% and 9.50% were AGA and LGA, respectively. Parity was a confounding factor influencing the incidence of LBW, while maternal age did not present a significant correlation. Pregnancies with severe preeclampsia were found to have a 29-fold increased likelihood of delivering LBW babies compared to the control group when controlling for parity (P=0.000, CI 95%). Hence, women with severe preeclampsia pregnancies have a higher risk for delivering LBW babies of 29 times higher than the control.
Keywords: Battaglia and Lubchencho; fetal growth restriction; low birth weight; severe preeclampsia; uteroplacental insufficiency